1989
DOI: 10.5636/jgg.41.727
|View full text |Cite
|
Sign up to set email alerts
|

A midday bite-out event of the F2-layer observed by MU radar.

Abstract: except the northernmost station, Wakkanai, and most prominently at Kokubunji. It occurred slightly earlier at higher latitudes. These facts suggest that the event was caused by poleward neutral winds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 8 publications
4
18
1
Order By: Relevance
“…This result is similar to those reported by Khan et al (1985) and Saryo et al (1989). In fact both Khan et al (1985) and Saryo et al (1989) attributed the bite-outs they observed to poleward/equatorward neutral winds after ruling out vertical E × B drifts due to the fact that the observing stations were outside of the equatorial anomaly region and the structures were propagating equatorward and thus cannot be originating from enhancement of the equatorial eastward/westward electric field. Both studies reached the conclusion that poleward/equatorward Figure 6.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This result is similar to those reported by Khan et al (1985) and Saryo et al (1989). In fact both Khan et al (1985) and Saryo et al (1989) attributed the bite-outs they observed to poleward/equatorward neutral winds after ruling out vertical E × B drifts due to the fact that the observing stations were outside of the equatorial anomaly region and the structures were propagating equatorward and thus cannot be originating from enhancement of the equatorial eastward/westward electric field. Both studies reached the conclusion that poleward/equatorward Figure 6.…”
Section: Discussionsupporting
confidence: 80%
“…The time difference between a decrease in hmF2 and a decrease in NmF2 of the bite-out structures observed over HE13N, MU12K and PQ052 ranges from 45 min to 1.75 h, 45 min to 1.50 h and 1.25 to 2.25 h respectively. These delays are slightly longer than those reported by Saryo et al (1989), who found a time delay of about 30 min between the decrease of hmF2 and foF2 bite-outs in their study. The decrease of hmF2 prior to NmF2 bite-outs seems to indicate that the descent of hmF2 to altitudes where the dissociative recombination rate of oxygen ion is higher results in plasma depletions observed as biteout structures.…”
Section: Resultscontrasting
confidence: 53%
See 2 more Smart Citations
“…3, which is different from Fig. 14 in Nakanishi et al (2014). This characteristic may have come from the phenomenon called "Midday Bite-Out event of the F2-layer" where the electron density is anomalously depressed at middle and low latitudes in the daytime due to a poleward neutral wind (Saryo et al 1989). We note that the LT variation of the meridional component of average MR amplitude shows a similar "bite out" around noon.…”
Section: Confirmation Of Previous Climatological Resultsmentioning
confidence: 75%